Pathological manifestations of granulomatous lobular mastitis - Cui, Leyin; Sun, Chenping; Guo, Jierong; Zhang, Xuliu; Liu, Sheng (Frontiers in Medicine, 2024)
Granulomatous lobular mastitis (GLM) is a rare inflammatory breast disease with unknown etiology, characterized by non-caseous granulomatous inflammation of the lobules of the breast, which infiltrate lymphocytes, neutrophils, plasma cells, monocytes, and eosinophils may accompany. GLM is often misdiagnosed as breast cancer due to the lack of specificity in clinical and imaging examinations, and therefore histopathology is the main basis for confirming the diagnosis. This review provides an overview of the pathological features of granulomatous lobular mastitis and cystic neutrophil granulomatous mastitis (CNGM, a pathologic subtype of GLM). As well as pathologic manifestations of other breast diseases that need to be differentiated from granulomatous lobular mastitis such as breast tuberculosis, lymphocytic mastopathy/diabetic mastopathy, IgG4-related sclerosing mastitis(IgG4-RSM), nodular disease and Wegener's granulomatosis, and plasma cell mastitis. Besides, discusses GLM and CNGM, GLM and breast cancer, emphasizes that their relationship deserves further in-depth exploration. The pathogenesis of GLM has not yet been clearly articulated and needs to be further explored, pathology enables direct observation of the microscopic manifestations of the disease and contributes to further investigation of the pathogenesis.